Birth Order Theory related to Emotional Intelligence development - Villanueva Iglesias, Marina; García-Martín, Judit (Revista Fuentes, 2023)
For many years psychologists have been examining the relation between the Birth Order Theory and personality features, without taking into account an essential psychological construct, Emotional Intelligence (EI). That is why this present study analyses the existent relation between this last psychological variable, which mainly shows the amount of control people are used to have dealing with their emotions, and the position held at birth. This last Theory is based on the idea of Birth Order, considering if someone was born the first one or maybe the second or even third (and more). This has been executed through the design and implementation of an ad hoc online questionnaire to a sample of 203 participants, in which 50 of them are men and 153 are women. Once the questionnaire is done, its results are revised and analysed. The results have shown that there are statistically significant differences in four fundamental psychological variables: emotion regulation, confrontation, self-control, and affective empathy, being able to establish that second borns tend to develop a better EI. These differences are shown mainly between the firstborn and the second or third child to be born. Finally, these results are discussed to establish conclusions and raise possible lines of future investigations in this educational psychological field.